The Role of Millenial Teacher in Conserving and Promoting Local Folklore through Student Centered Learning - Fajar, Dwi Ario (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The objective of this study is to explain the role and strategy of the teachers in teaching and learning of folklore in industrial revolution 4.0 era. Folklore as the part of local wisdom needs to be conserved and promoted. Millennial generation is the key of the success in conserving and promoting local folklore. Indonesia has potential students as millennial generation must be taken advantage in education. This research helps the teachers and educators to teach and learn the local folklore in industrial revolution 4.0 era through millennial generation. This study tries to maximize the Student Centered Learning approach in developing the use of e-learning and social media.